2009
DOI: 10.1590/s0034-89102009005000058
|View full text |Cite
|
Sign up to set email alerts
|

Inatividade física no lazer de adultos e fatores associados

Abstract: OBJECTIVE:To analyze the association between leisure-time physical inactivity and sociodemographic factors and risk or protection factors for chronic noncommunicable diseases among adults. METHODS:Cross-sectional study comprising adults aged 18 years and older (n = 1,996). Data was obtained from the Surveillance System for Risk Factors for Chronic Noncommunicable Diseases (CNCDs), a random-digit-dialed telephone survey carried out in the city of Florianópolis, southern Brazil, in 2005. There were studied socio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0
14

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 22 publications
3
9
0
14
Order By: Relevance
“…21 Studies have shown that lower levels of education are associated with less physical activity. 22,23 This scenario may contribute to worsening health conditions among individuals of lower socioeconomic status, which is evident in studies on inequalities in health. 24 The association between functional incapacity and physical inactivity was positive and statistically significant, showing the importance of performing physical activities in order to maintain functional capacity.…”
Section: Discussionmentioning
confidence: 99%
“…21 Studies have shown that lower levels of education are associated with less physical activity. 22,23 This scenario may contribute to worsening health conditions among individuals of lower socioeconomic status, which is evident in studies on inequalities in health. 24 The association between functional incapacity and physical inactivity was positive and statistically significant, showing the importance of performing physical activities in order to maintain functional capacity.…”
Section: Discussionmentioning
confidence: 99%
“…32 Estudos 33 e 54,6% em Florianópolis (Santa Catarina). 34 Em Pelotas (Rio Grande do Sul), município vizinho ao do presente estudo, a prevalência de inatividade física no lazer foi de 69,8%, 35 valor inferior aos 74,3% dos pacientes que se apresentaram inativos, no domínio do lazer, no período anterior à internação. A prática regular de atividade física no lazer é somente uma das dimensões da atividade física, sendo recomendada a sua realização em vários setores da vida diária, incluindo também atividades ocupacionais, deslocamento e atividades domésticas.…”
Section: Resultsunclassified
“…O sedentarismo é um fator de risco para a obesidade tão importante quanto o consumo de dieta inadequada, e possui uma relação direta e positiva com o aumento da incidência do diabetes mellitus do tipo 2 em adultos, independentemente do Índice de Massa Corporal (IMC), ou de história familiar de diabetes mellitus, sendo assim o papel do exercício físico como umas das principais estratégias/meio para o tratamento dessa doença é fundamental. 17,18 Entre os fatores que podem influenciar a resposta ao exercício físico, estão os determinantes genéticos, diferenças na idade, biotipo, aptidão física, duração e modalidade do exercício físico. 19 Um estudo realizado em 1985 já demonstrou que o efeito do exercício físico sobre o controle da glicemia pode ser efêmero, obtendo-se queda da glicemia pós-exercício físico e seu retorno rápido aos níveis pré-exercício físico com a suspensão do exercício.…”
Section: Discussionunclassified